Development of a learning media model for basic soccer techniques through comic books - Tegar Arif Wibowo; Hardopo Putro, Kukuh; Intan Erlita; Fateh Maulana Jaffar Nadri; Muharama Afanza; Patricia Vina Putri Maulani; Rifky Nur Hidayat; Robith Syaifullah Wijaya; Ferlin Dwi Nugroho; Rendi Cahya Trikusuma; Fitri Nur Azizah; Prasetya Annaufa Romi Pratama (Jorpres (Jurnal Olahraga Prestasi), 2025)
The objective of this research is to produce a comic media product of football basic techniques that is suitable to use by athletes that can facilitate the way of learning and practicing football basic technique movements.This research was a research and development using Sugiyono's development procedure with 8 steps: (1) Potential problems, (2) Collecting materials, (3) Product design, (4) Product creation, (5) Validation of material and media experts, (6) Product revision, (7) Product trial, and (8) Final product. Small group product trials were conducted at Real Madrid Foundation UNY with coaches and athletes totaling 12 subjects. Large group product trials were conducted at SSB Maguwoharjo Putra and Maguwoharjo Football Park totaling 34 subjects. The data analysis techniques used descriptive statistical analysis by finding the average score.The research findings reveal that the football basic technique media developed is suitable to use in learning. The results of the validation of material experts are at 3.3 (Good) and the validation of media experts is at 4.6 (very good). The results of the small group trial of coaches are at 4.8 (very good) and athletes are at 4.5 (very good) while the results of the large group trial of coaches are at 4.4 (very good) and athletes are at 4.6 (very good). Comic media of football basic techniques can attract the interest and motivation of beginner athletes to learn football basic techniques and enrich the varieties in the training media.